Turning the Mirror : A Conversation with Pankaj Mishra. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and award-winning writer Pankaj Mishra.They discuss several of Pankaj's books, including From the Ruins of Empire: The Intellectuals Who Remade Asia and An End To Suffering: The Buddha In The World, and his motivations behind them. This carefully-edited book includes an introduction, The Weight of History, and questions for discussion at the end of each chapter. Howard Burton was the Founding Director of Canada's Perimeter Institute for Theoretical Physics. He holds a PhD in theoretical physics and an MA in philosophy.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. A Different Perspective -- II. Demanding a Response -- III. Inseparable Factors? -- IV. East and West -- V. Discovering Buddhism -- VI. Personal Examinations -- VII. At an Impasse -- VIII. Learning From the Past -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Mishra, Pankaj -- Interviews; Mishra, Pankaj; Interviews